Phytochemical Screening and Determination of Total Phenolic, Total Flavonoids Content ff Water and Ethanol Extract of Dayak Onion Bulbs (Eleutherine Americana Merr) - Dinata, Reviana Amalia; Ayu Mentari, Ika; Hairunisa, Indah; Mariana Kustiawan, Paula (Universitas Muhammadiyah Kalimantan Timur, 2024)
Free radicals are molecules that are inconsistent and reactive because they have a portion of the electron that does not have a mate. Free radicals in the body that exceed their capacity will result in oxidative stress. Oxidative Stress can induce damage to various instruments in cells, such as carbohydrates, proteins, DNA, and fat. If oxidational stress is not handled properly, then it will cause degenerative disease. Free radicals can be overcome with antioxidant compounds. Dayak onions (Eleutherine americana (L.) Merr) are suspected to contain flavonoids and phenolic substances that can be antioxidants. The study aims to determine the content of secondary metabolites, total phenolic levels, as well as the flavonoids of the water extract and the ethanol extract of Dayak onions (Eleutherine americana (L.) Merr) obtained from Tenggarong Seberang (L3), East Kalimantan. The method used to determine total phenolic levels using the Folin-Ciocalteu method, the determination of total flavonoid levels using the colorimetric method, as well as phytochemical screening tests using the tube method. Results obtained at the total phenolic content of dayak onions water extract 0.45±0.07 mg GAE/g and dayak onions ethanol extract 1.21±02.02 mg GAE/g, as well as the total level of flavonoids in dayak onions aquatic extracts 1.17±0.66 mg QE/g and dayak onions etanol extraction 1.33±0.41 mg QE/g, from such results indicate higher total levels of phenolics and flavanoids found in dayak onions ethanol extracted.